2019
DOI: 10.1111/exsy.12420
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for a 360° information system model for private health care organizations

Abstract: At a time when communication, new media, and digitalization are transversal to the whole of society, private health care organizations have the possibility of making their business processes evolve. The objective is thus to seize the benefits associated to the active use of patients' electronic health records (EHRs) as the basis for personalized health care. In order to initially validate the health care sector acceptance of a 360°health care information system (HIS), focused on collecting patients' data to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Both patients and organizations will benefit from the emotional introduction of e-healthcare systems. Private and public health organizations, which promote physical health and emotional well-being, would have the capacity of offering their customers/patients improved quality of services (Magalhães et al , 2020). Doctors, nurses, and other hospital personnel need to be addressed and trained in their working atmosphere for new events and information.…”
Section: Introductionmentioning
confidence: 99%
“…Both patients and organizations will benefit from the emotional introduction of e-healthcare systems. Private and public health organizations, which promote physical health and emotional well-being, would have the capacity of offering their customers/patients improved quality of services (Magalhães et al , 2020). Doctors, nurses, and other hospital personnel need to be addressed and trained in their working atmosphere for new events and information.…”
Section: Introductionmentioning
confidence: 99%
“…Those studies found that there is a significant difference between age and the factors related to the acceptance model of information use technology (F = 5.018). According to the Scheffe test, people under 30 years old (M = 81.48 ± 13.16) are more sensitive to cognitive usefulness than those aged 31–40 years (M = 73.82 ± 12.66) and 41–50 years (M = 81.48 ± 13.16), indicating that younger people are more likely than older people to agree that an information system is useful [ 34 ]. Another study pointed out that nurses at the N level have more positive acceptance of nursing information usage than nurses at the N1 and N2 levels (F = 3.95).…”
Section: Discussionmentioning
confidence: 99%
“…Much of this difficulty was due to the complexity of the system and the permanent mutation of a large set of multi-level variables, together with a whole set of rationality principles based on a necessary cost-benefit analysis. To try to mitigate some of the difficulties, pilot projects or prototypes were developed whenever possible to reduce the risk associated with each change process (Magalhães et al, 2019).…”
Section: Agri-food Information Systems Architecture Proposalmentioning
confidence: 99%